2018
DOI: 10.4103/cytojournal.cytojournal_53_17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study of thyroid nodule cytopathology and histopathology at two institutions in Jordan

Abstract: Background:Fine-needle aspiration (FNA) plays a fundamental role in determining the appropriate management for patients presenting with thyroid nodules.Aims:The aims of this study are to evaluate thyroid FNA test performance parameters through a cytohistological correlation.Materials and Methods:A retrospective analysis of all thyroid FNAs received over a period of 18 months was carried out. The findings were compared to their subsequent definite diagnoses on surgical specimens as well as to their follow-up re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
(51 reference statements)
1
11
0
1
Order By: Relevance
“…A high prevalence of thyroid cancer was seen in our patients with thyroid nodules (13.4% of the females and 18.4% of the males), and there was no significant difference in the rate of cancer among those with single nodules and multiple nodules (P value = 0.07); this is similar to what was reported by Frates et al [16], and the highest rate of cancer was among those with nodules 1-2 cm in size; this is similar to a study that showed the highest malignancy rate among nodules < 2 cm in size [17]. The overall prevalence of cancer among patients with thyroid nodules was 13.8%, which is higher than that in neighboring countries, which is reported to be approximately 9-10% [8][9][10]. TSH level was significantly associated with thyroid cancer (P -value 0.01), which is consistent with studies that showed an increased risk of thyroid cancer with an increase in TSH level [12,18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A high prevalence of thyroid cancer was seen in our patients with thyroid nodules (13.4% of the females and 18.4% of the males), and there was no significant difference in the rate of cancer among those with single nodules and multiple nodules (P value = 0.07); this is similar to what was reported by Frates et al [16], and the highest rate of cancer was among those with nodules 1-2 cm in size; this is similar to a study that showed the highest malignancy rate among nodules < 2 cm in size [17]. The overall prevalence of cancer among patients with thyroid nodules was 13.8%, which is higher than that in neighboring countries, which is reported to be approximately 9-10% [8][9][10]. TSH level was significantly associated with thyroid cancer (P -value 0.01), which is consistent with studies that showed an increased risk of thyroid cancer with an increase in TSH level [12,18].…”
Section: Discussionsupporting
confidence: 91%
“…Other countries with high incidence rates include the USA (13.2), Canada (12.7), Turkey (10.9) and Italy (10.8) [6,7]. Other studies from the Middle East showed thyroid cancer in 10.5% of patients with thyroid nodules in Jordan [8] and rates of 5% in Saudi Arabia in one study [9] and 10.4% in another [10]. In the United Arab Emirates, the prevalence was 9% among those of Emirati origin [11] and 5% among those with thyroid nodules in Pakistan [12].…”
Section: Introductionmentioning
confidence: 99%
“…The classification systems provides to use the same terminology which predicts the correct malignancy rates. There were numerous study in the literature about the using TBSRTC (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Three of them had lower rates for B3 and seven of them for B4. The remaining of them were in normal rates (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The current study's malignancy rates were 6.8% 32.8% (high), 52.1% (high), 66.8% (normal) and 97.5% (normal).…”
Section: Discussionmentioning
confidence: 99%
“…Arul et al realiza un estudio con 528 pacientes que presentaron nódulo tiroideo y fueron puncionados,403 casos fueron diagnosticados como benignos (Bethesda II 76%), 67 fueron Bethesda III (12.6%), 36 casos como Bethesda IV (6%) mientras que 22 casos fueron categorizados ya sea maligno o sospechoso de malignidad (Bethesda V y VI que representa el 4%) [15]. Sughaver en el 2018 publica un estudio con 499 casos de nódulos tiroideos que fueron puncionados; se encontró una interpretación benigna en 273 pacientes (54.7%), atipia de importancia indeterminada en 81 (16.2%), neoplasia folicular en 20 (4%), sospechosa de malignidad en 36 (7.2%), maligna en 32 (6.4%) y no diagnósticos en 57 pacientes (11.4%) [16] Malukani et al en el 2018 realiza un estudio con 606 casos y cuyos resultados son: Categoría I: 26 (4.29%), Categoría II: 501 casos (82.67%), Categoría III: 5 (0.82%), Categoría IV: 55 (9.07%), Categoría V: 7 (1.15%) y Categoría VI: 12 (1.98%) [17].…”
Section: Discussionunclassified